Analysis of the dimensions of health service quality towards the satisfaction of outpatient BPJS patients at the Plus Perbaungan Health Center, Serdang Bedagai Regency - Silfani, Dellya; Nurhayati, Nurhayati; Eliska, Eliska (Science Midwifery, 2025)
The problems of BPJS health services that are often complained about until now are the rejection of BPJS patients and long service times, unfriendly doctor and nurse services, and drug administration services that are still long when compared to non-BPJS patients. The purpose of this study was to analyze the dimensions of health service quality on the satisfaction of BPJS outpatients at the Perbaungan Plus Health Center in Serdang Bedagai Regency. This study is a quantitative study using a cross-sectional study design. This study was conducted from January to March 2025. A total of 95 BPJS outpatients at the Perbaungan Plus Health Center were selected as respondents through accidental sampling techniques using the slovin formula. Data were collected through questionnaires and analyzed using Chi Square. The results of the chi square statistical test showed that there was a relationship between responsiveness and patient satisfaction p-value 0.01, empathy with patient satisfaction p-value 0.04. Then, the variables reliability, assurance and tangible were not related to patient satisfaction in BPJS outpatients at the Perbaungan Plus Health Center. The dimensions of health service quality that most dominantly influence the intention of repeat visits of BPJS outpatients at the Perbaungan Plus Health Center are the responsiveness dimension and the empathy dimension with a p-value <0.05.